2011
DOI: 10.12741/ebrasilis.v4i2.85
|View full text |Cite
|
Sign up to set email alerts
|

Mass Trapping and Classical Biological Control of Rhynchophorus palmarum L. 1794 (Coleoptera: Curculionidae). A hypothesis based in morphological evidences.

Abstract: Abstract. Palm weevils have been reported as a pest and red ring nematode vectors for several palms of the Arecaceae family. Rhynchophorus palmarum L (Coleoptera: Curculionidae) is a pest for coconut crop and other palms. It is vector of Bursaphelenchus cocophilus (Cobb) Baujard (Nematoda) etiological agent of Red Ring disease and other nematodes. Current methods recommended use of enemies and parasites in integrated pest management of Rhynchophorinae. In addition, mass trap reduce environmental damage. The ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 16 publications
0
8
0
2
Order By: Relevance
“…The only non-fungal ITS sequence obtained from one of these dauers was also of poor quality with many ambiguous base calls; the closest match was to Ditylenchus sp. This contamination issue was not too surprising because Miguens (2011) had reported that R. palmarum was highly infected by a fungus.…”
Section: Resultsmentioning
confidence: 99%
“…The only non-fungal ITS sequence obtained from one of these dauers was also of poor quality with many ambiguous base calls; the closest match was to Ditylenchus sp. This contamination issue was not too surprising because Miguens (2011) had reported that R. palmarum was highly infected by a fungus.…”
Section: Resultsmentioning
confidence: 99%
“…The occurrence of higher density patches (20 to 100 individuals) may be due to pheromone aggregation produced by these beetles [ 63 ]. In addition, synergism can occur between the volatiles of corn ears with sexual and aggregation pheromones enhancing insect responses to these compounds and favoring feeding, mate finding, and mating [ 64 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pheromone traps remains the focus of most research investigations during the last few decades (Ávalos and Soto, 2015;El-Shafie et al, 2011;Fiaboe et al, 2011;Hamidi et al, 2013;Hoddle et al, 2013;Miguens et al, 2011;Perez et al, 1996). Pheromone traps are being used in date palm plantations since 1990s.…”
Section: Pheromone Trapsmentioning
confidence: 99%